Administração da associação de dexmedetomidina e ropivacaína 0,75% em bloqueios dos nervos isquiático e femoral guiados por ultrassom e por neuroeletroestimulação em cães - Trein, Thomas Alexander [UNESP] (2015)
The study aimed to evaluate the effects of administration of ropivacaine 0.75% combined with dexmedetomidine on the sciatic and femoral nerves in dogs. Seven adult and healthy Beagle dogs were submitted to three experimental groups. In GCON, animals received perineural ropivacaine 0,75% (0.1mL/kg/nerve); GDPN received perineural dexmedetomidine diluted (1μg/mL) in ropivacaine 0,75% (0.1mL/kg/nerve); and GDIM received perineural ropivacaine 0,75% (0.1mL/kg/nerve) and dexmedetomidine diluted in saline (1μg/mL) via intramuscular administration (0,2mL/kg). The perineural administrations were carried out under general inhalation anesthesia and guided by ultrasound and nerve stimulation. Onset time and duration of sensory and motor blocks were evaluated, as well as patellar, gastrocnemius and cranial tibial reflexes, heart (FC) and respiratory rate (f), systolic arterial pressure (PAS), rectal temperature (TR), lactate (LACT), blood glucose (GLIC), sedation (SED) and blood gas analysis during 240 minutes. No differences were observed between groups with regards to FC, f, PAS, LACT, GLIC, TR, SED, blood gas, reflexes and sensory and motor block latency. However, the duration of the tibial sensory block was significantly longer in GDPN compared with GDIM (p=0,0302). Administration of perineural or intramuscular dexmedetomidine did not cause changes in physiologic parameters or the onset time and duration of motor block. The perineural administration of dexmedetomidine prolonged the duration of the sensory block only for the tibial nerve.